DEMONSTRATION AND EVALUATION OF EFFECT OF WEEDICIDES ON BROAD LEAVED WEEDS ON WHEAT YIELD - A. U. Malik; I. Hussain; M. Ahmad alias H. A. Bakhsh; M. A. Haji; M. Ali (Journal of Animal and Plant Sciences, 2009)
A series of field trials were conducted to evaluate the effect of newly introduced weedicide against broad leaved weeds of wheat crop at Adaptive Research Farm, Rakh Chabbri Zareen D.G.Khan during the years 2005-06 to 2007-08. The treatments included: Control/Check (T1); Pendimethalin @ 1250 ml ha-1 (T2); Buctril-M @ 2500 ml ha-1 (T3); Logran @ 250 g ha-1 (T4); MCPA @ 1250 ml ha-1 (T5); Bromoxonil @ 1250 ml ha-1 (T6). The results revealed that weed management strategies significantly improved the yield and yield parameters during all the three years of experimentation as compared to weedy check (T1). The highest grain yield (3024 Kg ha-1) was observed, when Buctril-M was sprayed at its recommended dose in year 2007-08, while the same trend of yield ha-1 was observed during rest of the study years (2256 Kg ha-1 & 2344 Kg ha-1 in year 2005-06 & 2006-07, respectively). Increase in yield was justified by the more number of tillers 261.0 m-1 (2005-06), 263.0 m-1 (2006-07) and 262.3 m-1 (2007-08), more number of grains per spike; 42.0 (2005-06), 43.0 (2006-07) and 43.3 (2007-08) and 1000-grains weight: 44.0 g (2005-06), 45.0 g (2006-07) and 40.2 g (2007-08) during the given period of study. So, it is concluded that broad leaf weeds in wheat crop can be controlled and managed well with the application of Buctril-M @ 2500 ml ha-1.
Keywords: wheat; weeds; weedicide; broad leaf weeds